Performance Level Of Scout Leaders Indicated By Their Most Important Leadership Qualities And Decision-Making Abilities - Watheq Hadood Obaid; Mazen Mohammed Habib (Musamus Journal of Physical Education and Sport (MJPES), 2026)
The current research aims to identify performance level of scout leaders at universities of Middle Euphrates region during academic year 2025-2026. The researchers used a descriptive approach with a survey method and correlational analysis. A sample of 40 scout leaders and 100 scouts was selected, as scout leadership is considered one of the most important and fundamental elements in success of scouting activities, and without it, other scouting elements cannot succeed. Competent leadership can understand requirements and developments during scouting activities through ability to make decisions and use successful and rapid communication skills by scout group to ensure speed and accuracy of implementing scouting activities . The researchers hypothesized that there is a significant correlation between performance level of leaders and the most important leadership qualities preferred by scout leaders, as well as decision-making. Importance of current research lies in attempting to analyze and track performance level of scout leaders in Iraqi universities from their perspective, while also providing scientific measures for leadership qualities and appropriate decision-making for scout leaders in universities. The researchers concluded that there is a consensus among the sample of scout leaders regarding the level of performance, there is a consensus among the sample of scout leaders in identifying the most important leadership qualities of scout leaders, the relationship between the leadership qualities variable and the decision-making variable for the sample of scout leaders depended on the relationship between their performance level. The researchers also recommends that need to adopt the performance level of scout leaders that the researcher reached in order to identify scout leaders in Iraqi universities and generalize it to the general directorates of education, paying attention to scout leaders and developing their abilities and skills through training courses and scout camps.